1995
DOI: 10.1136/ard.54.8.640
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral CD8 lymphocytes and soluble IL-2 receptor in predicting the duration of corticosteroid treatment in polymyalgia rheumatica and giant cell arteritis.

Abstract: Objectives-To determine if the presence of low percentages of CD8 positive cells or high levels of soluble interleukin-2 receptors (sIL-2R) define a subgroup of patients with more severe polymyalgia rheumatica and giant cell arteritis (PMR/GCA). Methods-38 PMR/GCA patients were followed up prospectively. Serum levels of sIL-2R and peripheral blood CD8 lymphocytes were measured before the start of corticosteroid treatment, after six months of treatment and at the last visit. Phenotypical analysis of lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…Several reports have demonstrated that CD8 + T cells are decreased, and CD4 + and naive (CD4 + CD45RA + ) T cells are increased in the active phase of PMR on flow cytometry (18)(19)(20). The present patient also showed improvement of clinical symptoms in parallel with an increase in CD8 + CD25 + cells and a decrease in CD4 + CD25 + cells and CD4 + CD45RA + cells.…”
Section: Discussionsupporting
confidence: 61%
“…Several reports have demonstrated that CD8 + T cells are decreased, and CD4 + and naive (CD4 + CD45RA + ) T cells are increased in the active phase of PMR on flow cytometry (18)(19)(20). The present patient also showed improvement of clinical symptoms in parallel with an increase in CD8 + CD25 + cells and a decrease in CD4 + CD25 + cells and CD4 + CD45RA + cells.…”
Section: Discussionsupporting
confidence: 61%
“…The longer duration of corticosteroid treatment observed in women by Chuang et al 23 has not been confirmed by other studies 910 A reduced percentage of CD8 cells after six months of treatment has also been proposed as a useful outcome parameter 24. However, Corrigall et al found that the %CD8 T cell was not a good indicator of disease activity 25…”
Section: Discussionmentioning
confidence: 94%
“…In general, <5% of tissue-infiltrating cells are CD8 + (31, 32). Reports more than 25 years ago had alerted the community to a selective loss of circulating CD8 T cells, both in percentage and absolute numbers (33–36), with activation markers expressed on remaining CD8 T cells (37). The recent study by Samson et al confirms the polyclonal stimulation of CD8 T cells and points towards higher representation of tissue CD8 T cells in cases of more severe vasculitis (31).…”
Section: Introductionmentioning
confidence: 99%